Analysis of Flashcard Game Activities on Early Reading Abilities of Children Aged 4-5 Years - Solihah, Enok; Sari, Novita; Yustika Rini, Ratu; Nur, Maulida; Parta Wibowo, Tito (JOYCED: Journal of Early Childhood Education, 2025)
Early reading ability is a fundamental skill that must be developed in early childhood as it forms the foundation for subsequent learning stages. This qualitative descriptive study aimed to analyze the implementation of flashcard game activities and their impact on early reading abilities of children aged 4-5 years at PAUD Al Adnan, Serang City. The research employed observation, semi-structured interviews, and documentation as data collection techniques, involving 10 children in Group A (6 boys and 4 girls) and their classroom teacher. Data analysis followed the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings revealed that flashcard games significantly enhanced children's letter recognition, phonological awareness, and simple word reading abilities. The visual, auditory, and kinesthetic aspects of flashcards effectively facilitated meaningful and enjoyable learning experiences. Children demonstrated increased motivation, active participation, and improved ability to recognize letters, pronounce syllables, and read simple words. However, individual differences in concentration levels, language development, and learning pace required differentiated instructional approaches. This study confirms that flashcards serve as effective educational game media in stimulating early reading development in young children when implemented with consistent repetition, appropriate guidance, and positive reinforcement from teachers.